Intraspecific variation of a desert shrub species in phenotypic plasticity in response to sand burial. Issue 4 (15th May 2013) - Xu, Liang; Huber, Heidrun; During, Heinjo J.; Dong, Ming; Anten, Niels P. R.
Summary Shoot elongation is one of the main plastic responses of plants to burial, a ubiquitous stress factor in dry ecosystems. Yet, intraspecific variation in this response to burial and the extent to which this variation is functionally coordinated with variation in other trait responses are largely unknown. We subjected seedlings of the shrub Caragana intermedia from 18 maternal parents (i.e. different half‐sib families) to repeated partial burial to investigate how burial affects shoot growth, stem mechanical traits and associated plasticity. Burial increased both stem elongation and diameter growth of plants, but decreased biomass production. Half‐sib families had different rates of shoot elongation, and differed in their response to burial with respect to biomechanical stem properties. Across half‐sib families, the magnitude of these responses in mechanical traits was positively correlated with the magnitude of the stem elongation response. These results indicate that plasticity in different stem traits in response to sand burial and intraspecific variation therein are functionally coordinated with respect to mechanical stability. The results emphasize the importance of considering functionally coordinated traits when analyzing phenotypic plasticity in plants.